A rare variant of first branchial cleft fistula (Bangladesh Journal of Otorhinolaryngology, 2011)
Objective: To report an extremely rare variant of first branchial cleft anomaly.Case report: A-13-year old boy presented with the chief complaint of persistent right aural discharge since infancy. On examination, a 1 mm fistulous opening was present in the floor of cartilaginous portion of external auditory canal. And scanty watery discharge came out through this opening when the patient asked to swallow. Sinogram through discharging meatal opening showed a thick irregular tract about 5 cm length traversing the soft tissue of neck extending from the floor of right external auditory canal to the lateral pharyngeal wall and spillage of contrast into the oral cavity.Conclusion: This was an extremely rare variant of first branchial cleft fistula. Due to the rarity of this disease, clinical misdiagnoses and inappropriate management may lead to recurrence and complications. For better prognosis, appropriate diagnosis and surgical planning are very important. Key words:  Objective: To report an extremely rare variant of first branchial cleft anomaly. Case report: A-13-year old boy presented with the chief complaint of persistent right aural discharge since infancy. On examination, a 1 mm fistulous opening was present in the floor of cartilaginous portion of external auditory canal. And scanty watery discharge came out through this opening when the patient asked to swallow. Sinogram through discharging meatal opening showed a thick irregular tract about 5 cm length traversing the soft tissue of neck extending from the floor of right external auditory canal to the lateral pharyngeal wall and spillage of contrast into the oral cavity. Conclusion: This was an extremely rare variant of first branchial cleft fistula. Due to the rarity of this disease, clinical misdiagnoses and inappropriate management may lead to recurrence and complications. For better prognosis, appropriate diagnosis and surgical planning are very important. Key words: First branchial anomaly; branchial cleft fistula; branchial cyst; fistulography. DOI: 10.3329/bjo.v17i1.7633 Bangladesh J Otorhinolaryngol 2011; 17(1): 72-75. DOI: 10.3329/bjo.v17i1.7633 Bangladesh J Otorhinolaryngol 2011; 17(1): 72-75